Improving Goat productivity in the humid zone of the tropics - Omeke, B.C.O. (1988)
Preliminary evaluation of the traditional management systems practiced in rearing west African Dwarf goats in Ayangba area of Benue State indicated high goat population and mortality rate but low productivity. Free range (scavanging) dominated the three identified systems. Comparative field study of the Scavanging, Tethering and Confined stall-feeding systems, using 120 does between 12 and 24 months of age for 12 months (May 1982-1983), preferentially favoured confined stall-feeding; the other two systems could improve by modified health care and feed supplementation. Feed supplementation and health care significantly improved performance within and between management systems, including mean weight gain per year for does; confined stall-feeding is the management system of choice, although Scavanging and confined stall-feeding systems could be combinely practiced. Maximum productivity necessitates selection and upgrading of indigenous breeds, through the cooperation of veterinary extension staff and government agencies.